Hässeldala – a key site for Last Termination climate events in northern Europe. (2nd November 2016) - Wohlfarth, Barbara; Muschitiello, Francesco; L. Greenwood, Sarah; Andersson, August; Kylander, Malin; Smittenberg, Rienk H.; Steinthorsdottir, Margret; Watson, Jenny; Whitehouse, Nicola J.
Abstract : The Last Termination (19 000–11 000 a BP) with its rapid and distinct climate shifts provides a perfect laboratory to study the nature and regional impact of climate variability. The sedimentary succession from the ancient lake at Hässeldala Port in southern Sweden with its distinct Lateglacial/early Holocene stratigraphy (>14.1–9.5 cal. ka BP) is one of the few chronologically well‐constrained, multi‐proxy sites in Europe that capture a variety of local and regional climatic and environmental signals. Here we present Hässeldala's multi‐proxy records (lithology, geochemistry, pollen, diatoms, chironomids, biomarkers, hydrogen isotopes) in a refined age model and place the observed changes in lake status, catchment vegetation, summer temperatures and hydroclimate in a wider regional context. Reconstructed mean July temperatures increased between c.  14.1 and c.  13.1 cal. ka BP and subsequently declined. This latter cooling coincided with drier hydroclimatic conditions that were probably associated with a freshening of the Nordic Seas and started a few hundred years before the onset of Greenland Stadial 1 ( c.  12.9 cal. ka BP). Our proxies suggest a further shift towards colder and drier conditions as late as c.  12.7 cal. ka BP, which was followed by the establishment of a stadial climate regime ( c.  12.5–11.8 cal. ka BP). The onset of warmer and wetter conditions preceded the Holocene warming over Greenland by c.  200 years. Hässeldala's proxies thus highlight the complexity of environmental and hydrological responses across abrupt climate transitions in northern Europe.